1999
DOI: 10.1073/pnas.96.24.13886
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for multiple origins of woodiness and a New World biogeographic connection of the Macaronesian Island endemic Pericallis (Asteraceae: Senecioneae)

Abstract: The prevalence of woody species in oceanic islands has attracted the attention of evolutionary biologists for more than a century. We used a phylogeny based on sequences of the internal-transcribed spacer region of nuclear ribosomal DNA to trace the evolution of woodiness in Pericallis (Asteraceae: Senecioneae), a genus endemic to the Macaronesian archipelagos of the Azores, Madeira, and Canaries. Our results show that woodiness in Pericallis originated independently at least twice in these islands, further we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
136
3
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 125 publications
(148 citation statements)
references
References 29 publications
8
136
3
1
Order By: Relevance
“…Trait utility of plant habit in Macaronesia is additionally manifested by further shifts. Reversal to an herbaceous condition had not, however, been documented in Macaronesian plant groups after acquisition of bush-like forms once (Sonchus, Isoplexis, Aeonium group) or multiple times (Pericallis) (Kim et al, 1996;Panero et al, 1999;Mort et al, 2002;Bräuchler et al, 2004). We herein confirm reversal to an herbaceous condition in woody lineages of Echium (Böhle et al, 1996) and report for the first time three independent formations of annual species (E. bonnetii, E. pitardii, E. triste) in dry habitats of Macaronesia (Fig.…”
Section: Evolution Of Woodinesssupporting
confidence: 71%
See 1 more Smart Citation
“…Trait utility of plant habit in Macaronesia is additionally manifested by further shifts. Reversal to an herbaceous condition had not, however, been documented in Macaronesian plant groups after acquisition of bush-like forms once (Sonchus, Isoplexis, Aeonium group) or multiple times (Pericallis) (Kim et al, 1996;Panero et al, 1999;Mort et al, 2002;Bräuchler et al, 2004). We herein confirm reversal to an herbaceous condition in woody lineages of Echium (Böhle et al, 1996) and report for the first time three independent formations of annual species (E. bonnetii, E. pitardii, E. triste) in dry habitats of Macaronesia (Fig.…”
Section: Evolution Of Woodinesssupporting
confidence: 71%
“…Many phylogenetic studies, however, reveal that remarkable shifts from herbaceous to bush and tree-like species across different plant groups (taxonomic families) is the predominant pattern (see revisions in Carine et al, 2004;Vargas, 2007). Among the 1062 genera of Macaronesian vascular plants, secondary acquisition of woodiness has been documented by means of molecular phylogenetics in Sonchus (Kim et al, 1996), Pericallis (Panero et al, 1999), the Aeonium alliance (Mort et al, 2002), Sideritis (Barber et al, 2002), Tolpis (Moore et al, 2002), and Convolvulus (Carine et al, 2004). Remarkably, significant morphological diversity (as exemplified by growth habits), is found in 28 Macaronesian Echium species (Böhle et al, 1996), surpassing that of the remaining 40 continental relatives.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Pericallis comprises 14 species (Nordenstam 1978) and has been estimated to be 12-14 million years old (Panero et al 1999;Swenson and Manns 2003). Here, we study three Pericallis species occurring on the island of Tenerife, P. echinata, P. cruenta and P. tussilaginis.…”
Section: Study Speciesmentioning
confidence: 99%
“…Based on ITS sequences, it was shown that P. echinata and P. cruenta belong to a well-supported subgroup consisting only of herbaceous species. P. tussilaginis belongs to a sister group that also contains some woody species (Panero et al 1999;Swenson and Manns 2003). The species descriptions in recent floras (Hohenester and Welss 1993;Schönfelder and Schönfelder 1997;Bramwell and Bramwell 2001) are mainly based on the system of Schultz (1845Schultz ( -1846.…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation